Digital Innovation and Organizational Agility Towards Improving Business Performance In Digital Startup Companies In Indonesia - Icin Quraysin; Dira Rizki Amalina; Ely Mustofiyah; Eva Sofiaty; Sukma Pratama (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the influence of digital innovation and organizational agility on business performance in digital startup companies in Indonesia. The research approach used was quantitative with a survey method. The study population was employees at digital startup companies that have adopted digital technology, with a sample of 120 respondents selected using a purposive sampling technique. Data collection was conducted through a questionnaire with a Likert scale of 1–5. Data analysis used validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results showed that digital innovation had a positive and significant effect on business performance. Organizational agility also had a positive and significant effect on business performance. Simultaneously, digital innovation and organizational agility were proven to have a significant effect on business performance with a significant contribution. This indicates that the higher the company's ability to develop digital innovation and improve organizational agility, the better the resulting business performance. This study implies that digital startups need to strengthen their innovation strategies and increase organizational flexibility to face increasingly dynamic business competition in the digital era.